UPAYA GURU MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DALAM MATA PELAJARAN AL-QUR’AN HADITS DI MTs HASANUDIN SEMARAPURA - Dewi Muawwiya Sofyani; Ika ` Ratih Sulistiani; Fita Mustafida (VICRATINA, 2021)
Teachers play a very important role in the learning process of students, teachers as educators, mentors, and teachers for students, therefore teachers are responsible for the success of students' learning. In fostering students' learning interest in the need for motivation by teachers.  Motivation is important for students, where motivation plays a very important role in improving students' learning interests and learning achievements. Learning al-Qur'an hadith is a learning that rarely uses a variety of methods, so that students become saturated and lazy to learn therefore the need for motivation to arouse students' interest in learning the Qur’an hadith. Based on this background, the problem raised by the researchers is the efforts of teachers to increase students' learning motivation in the subjects of The Qur'an Hadith in MTs Hasanudin.  The purpose of this research is to describe the efforts of teachers to increase students' learning motivation in the subjects of the Qur'an hadith in MTs Hasanudin. The results showed that (1) the efforts of teachers to increase the motivation of grade VII students in the subjects al-1qur'an hadith in MTs Hasanudin has been implemented by creating interest in students' learning, applying variations in learning methods, creating fun learning experiences, giving praise and assessment and reward to students, and also creating competitive competition between students. (2) The increase in students' learning motivation is influenced by two things, namely, the level of awareness of the students and the atmosphere of the class. (3) inhibitory factors in an effort to increase students' learning motivation are divided into two things, namely internal and external factors, factors supporting teacher efforts to increase students' learning motivation, namely, school facilities and facilities that support learning. Kata Kunci: Upaya Guru, Motivasi Belajar, Mata Pelajaran Al-Qur’an Hadits